Mid-Term Survival and Risk Factors Associated With Myocardial Injury After Fenestrated and/or Branched Endovascular Aortic Aneurysm Repair. (October 2021) - Moussa, Mouhamed D.; Lamer, Antoine; Labreuche, Julien; Brandt, Caroline; Mass, Guillaume; Louvel, Paul; Lecailtel, Sylvain; Mesnard, Thomas; Deblauwe, Delphine; Gantois, Guillaume; Nodea, Madalina; Desbordes, Jacques; et al.
Abstract : Objective: Myocardial injury after non-cardiac surgery (MINS) is an independent predictor of post-operative mortality in non-cardiac surgery patients and may increase health costs. Few data are available for MINS in vascular surgery patients, in general, and those undergoing fenestrated/branched endovascular aortic repairs (F/BEVAR), in particular. The incidence of MINS after F/BEVAR, the associated risk factors, and prognosis have not been determined. The aim of the present study was to help fill these knowledge gaps. Methods: A single centre, retrospective study was carried out at a high volume F/BEVAR centre in a university hospital. Adult patients who underwent F/BEVAR between October 2010 and December 2018 were included. A high sensitivity troponin T (HsTnT) assay was performed daily in the first few post-operative days. MINS was defined as a HsTnT level ≥ 14 ng/L (MINS14 ) or ≥ 20 ng/L (MINS20 ). After assessment of the incidence of MINS, survival up to two years was estimated in a Kaplan–Meier analysis and the groups were compared according to MINS status. A secondary aim was to identify predictors of MINS. Results: Of the 387 included patients, 240 (62.0%) had MINS14 and 166 (42.9%) had MINS20 . In multivariable Cox models, both conditions were significantly associated with poor two year survival (MINS14: adjusted hazard ratio [aHR] 2.15, 95% confidence interval [CI] 1.10 – 4.19; MINS20 : aHR 2.43, 95% CI 1.36 – 4.34). In a multivariable logistic regression, age, revised cardiac risk index, duration of surgery, pre-operative estimated glomerular filtration rate (eGFR), and haemoglobin level were independent predictors of MINS. Conclusion: After F/BEVAR surgery, the incidence of MINS was particularly high, regardless of the definition considered (MINS14 or MINS20 ). MINS was significantly associated with poor two year survival. The modifiable predictors identified were duration of surgery, eGFR, and haemoglobin level. Graphical abstract: Image 1